EFFECT OF ANTIBIOTICS ON MESENCHYMAL STROMAL CELLS UNDER XENO-FREE CULTURE CONDITIONS FOR CLINICAL USE - JAIANAND KANNAIYAN; SHRADDHA SINGH GAUTAM (International Journal of Pharma and Bio Sciences, 2013)
Recent advances in regenerative medicines indicate that adult Mesenchymal Stromal Cells are promising candidates for cell-based therapies because of their large in vitro expansion potential. During this expansion one of the main questions is obtaining a perfect combination of antibiotics that can be used safely on cultures with minimum interference on cellular levels. Considering this basic need current investigation is designed to propose antibiotic combination with optimum concentration having minimum effect on cells characteristics. For the analysis we used four types of antibiotics with three different concentrations each; Amikacin, Gentamycin, Cefoperazone Sodium, Vancomycin. It is observed that Amikacin showed slight alterations in cell viability and morphology as compared to other antibiotics. Out of four antibiotics Vancomycin proved to be the best antibiotic followed by Gentamycin and Cefoperazone Sodium. Hence Vancomycin can be used along with the Gentamycin; Cefoperazone sodium being a third generation antibiotic can be used alone to avoid detrimental effect of other antibiotic on cell lines.